Assessment of VoF based numerical scheme for bubble rise in isothermal liquid layer, and some new insight in thermally stratified liquid layers. (April 2021) - Agarwal, Shashwat Sharad; Kumar, Kunal; Chandra, Laltu; Ghosh, Pradyumna
Abstract: This paper aims at (a) comparative assessment of the different volume of fluid (VoF) based numerical schemes for a rising, single air bubble in isothermal liquid (water) layers and (b) investigation of bubble rise in thermally stratified liquid (therminol) layers. For numerical investigation of bubble rise in isothermal liquid layers, three available numerical schemes, Upwind, Quadratic Upstream Interpolation for Convective Kinematics (QUICK) and Monotonic Upwind Scheme for Conservation Laws (MUSCL) schemes, combined with the pressure-velocity coupling( p-v ) approaches, such as, Pressure Implicit with Splitting of Operators (PISO) and Semi Implicit Method for Pressure-Linked Equations (SIMPLE), are considered. The wake analysis revealed that the region of influence grows beyond 10 times the diameter of the bubble. Moreover, based on the comparative assessment, MUSCL scheme with PISO is selected, for investigating the bubble rise in thermally stratified therminol layers. Based on these investigations, a 3D diagram, describing bubble shape as f ( Ra, Eo, Ga ), is proposed, and a new insight to the micro-convection, inside the rising bubbles is provided. Furthermore, a time-scale analysis is performed to describe the heat transfer mechanisms, (a) inside air bubble, and (b) between air bubble and the external surrounding liquid. Thus, the findings will be useful for the design of heat exchangers or cooling devices, which rely on the heat transfer augmentation with rising air bubble.